Local community's participation and empowerment level towards sustainable heritage tourism in Taiping, Malaysia - Abd Aziz, Mustafa; Johari, Shazali; Kunasekaran, Puvaneswaran (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The aim of this study is to holistically understand the role of community participation and resources in influencing the sustainable heritage tourism practice of the Taiping local community in Malaysia. Descriptive statistics used as the indicator of community participation and empowerment towards sustainable tourism practice. Overall, participation and empowerment levels were at a higher level. Although there is good level of participation, the empowerment level is not very high. This is most likely because of majority of the respondents were not involved in tourism and they were not empowered in tourism planning. The infrastructure development in Perak is still in infancy stage. Since Taiping is the second largest city in Perak, it is suggested that a public transport hub should be developed in Taiping so that it is easily accessed by tourists. Therefore, tourism stakeholders should work closely to promote Taiping as a tourist destination.